Supply chain contract design of procurement and risk-sharing under random yield and asymmetric productivity information. (December 2018) - Zhou, Caifeng; Tang, Wansheng; Lan, Yanfei
Highlights: We consider contract design of procurement and risk-sharing under random yield. The retailer cannot benefit from risk-sharing under symmetric information. Both the manufacturer and the retailer can benefit from risk-sharing under certain conditions. Risk-sharing can weaken (enhance) the effect of asymmetric information on the retailer (manufacturer). It is necessary to consider risk-sharing under random yield for the retailer. Abstract: When procuring from a manufacturer (she) with random yield, the retailer (he) is often reluctant to share the risk caused by this yield, while the manufacturer is not. However, if the manufacturer possesses private productivity information, the retailer may change his decision. To capture the interaction between risk-sharing and asymmetric information, we build a model in which the retailer designs a non-risk-sharing contract (a simple wholesale price contract) or a risk-sharing contract (a wholesale price contract with a subsidy) for the manufacturer given both random yield and private productivity information. The manufacturer's best response, the optimal contract menus and the supply chain participants' profits in each case are theoretically derived. By examining the value of risk-sharing, we find that the retailer cannot benefit from risk-sharing under symmetric information. Interestingly, under asymmetric information, risk-sharing benefits not only the manufacturer but also the retailer under certain conditions, resulting in a win-win situation for both the retailer and the manufacturer. Furthermore, we analyze the value of information, illustrating that asymmetric information always harms the retailer and benefits the manufacturer regardless of whether or not the retailer shares risk. However, risk-sharing can weaken (enhance) the effect of asymmetric information on the retailer (manufacturer). Additionally, we derive the optimal contract menus under deterministic yield and find that risk-sharing makes no significance.